Pengaruh Marketplace Maxim Terhadap Tingkat Penjualan Pada UMKM di Kota Gorontalo - Hajiku, Faradila; Niswatin; Yusuf, Nilawaty (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of the use of the Maxim marketplace application on the level of sales of MSMEs in Gorontalo City. This study uses a quantitative method using the SmartPLS 4 application. The population of this study were culinary MSMEs in Gorontalo City, who collaborated with the Maxim marketplace and the sample of this study was 90 using the Slovin technique. In this study, the data collection techniques used were observation, interviews and questionnaires. The results of this study indicate that the Maxim Marketplace has an effect on the level of sales of culinary MSMEs in Gorontalo City. This is because the results of the hypothesis test on the Maxim Marketplace variable show that the significant value is smaller than the partial results which indicate that the Maxim Marketplace has an effect on the level of sales with positive results, so the hypothesis is accepted. These results show that the use of the Maxim Marketplace as a marketing tool provides many advantages and benefits for both business actors and consumers, namely saving more time and money, easier to control the business, and having a wider reach in business competition in the global market.